Correction to: The aorta after coarctation repair – effects of calibre and curvature on arterial haemodynamics - Michael A. Quail; Patrick Segers; Jennifer A. Steeden; Vivek Muthurangu (Journal of Cardiovascular Magnetic Resonance, 2019)
In the original version of this article [1], published on 11 April 2019, there is 1 error in the ‘Conclusion’ paragraph of the abstract.